Tinjauan Hasil Riset Pada Badan Riset Dan Inovasi Daerah (Brida) Dalam Mendukung Pembangunan Kota Medan - Kholidah Lidya Lubis; Mutia Anggraini; Lilis Apriyaningsih (STIKes Ibnu Sina Ajibarang, 2024)
This study discusses the importance of the presence of research and innovation management institutions that are increasingly recognized along with the needs of the Government and local governments to resolve problems, development gaps and find solutions to regional government problems. This can be interpreted that BRIDA is not only transformed into a manager of supporting functions in the field of research and development as before but its presence is required to be able to fundamentally change the governance of research and development and increase its connectivity with the innovation system and global competitiveness. In the perspective of regional government policy, it is required to be able to formulate quality and evidence-based policies. This study aims to analyze the role of the Regional Research and Innovation Agency in supporting the development process of the city of Medan and supporting the development of the city of Medan. The method used in this study is a qualitative descriptive method. Data collection techniques in the form of observation and documentation. Based on the results of the study, it was obtained that the Regional Research and Innovation Agency has a policy formulation and strategy that supports the vision of developing the city of Medan into an innovative and highly competitive city. Then the Regional Research and Innovation Agency has great potential to continue to be the main driver of sustainable and innovative city development.